Finite Element Analysis on Block Shear Mechanism of Lean Duplex Stainless Steel Welded Connections - YongHyun Cho; Dong-Keon Kim; JunSu Kim; TaeSoo Kim (Applied Sciences, 2021)
The block shear equations specified in the current AISC specification for structural steel buildings and North American cold-formed steel design specifications are based on research results of carbon steel bolted connections. These equations were found to be inapplicable for the welded connections in the literature. This issue is primarily associated with the use of the incorrect assumption on block shear failure mechanism. The present paper examines the accuracy of various block shear equations available in the design specifications and in the literature. The paper also examines the shear hardening capacity and the level of tensile stress over the critical net area with the results of finite element analysis, in which the fracture simulation is considered. It shows that the block shear capacities of lean duplex stainless steel welded connections can be predicted accurately using tensile stress equal to 1.25Fu, as proposed in the literature.